2019
DOI: 10.1016/j.ijmecsci.2019.04.054
|View full text |Cite
|
Sign up to set email alerts
|

Damage characterizations and simulation of selective laser melting fabricated 3D re-entrant lattices based on in-situ CT testing and geometric reconstruction

Abstract: In recent years, metal additive manufacturing (AM) are widely employed for industrial applications, such as: biomedical, aerospace, automotive, marine and offshore sections. AM demonstrated superior manufacturing efficiencies and economic advantages for advanced lightweight industrial components with unlimited arbitrary topological layouts and complex internal microstructures, and are also employed for fabrication of auxetic materials and structures. In this paper, damage characterizations and mechanical behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…The developed meta-structures exhibited superior Young's modulus, collapse strength and energy absorption than traditional honeycomb structures. Geng et al [25] investigated mechanical response, damage initiation and failure evolution of metallic meta-materials fabricated by SLM 3D printing under quasi-static compression. The results showed that the failure behavior of the reentrant lattice is governed not only by its topology, but also by the geometric defects and surface defects.…”
Section: Introductionmentioning
confidence: 99%
“…The developed meta-structures exhibited superior Young's modulus, collapse strength and energy absorption than traditional honeycomb structures. Geng et al [25] investigated mechanical response, damage initiation and failure evolution of metallic meta-materials fabricated by SLM 3D printing under quasi-static compression. The results showed that the failure behavior of the reentrant lattice is governed not only by its topology, but also by the geometric defects and surface defects.…”
Section: Introductionmentioning
confidence: 99%
“…Lattice structures are formed mathematically or geometrically by spatial arrangement and combination of a grouping of unit cells. Most researchers focus on the mechanical properties, such as compression and tension behavior [1][2][3][4][5][6][7][8], fracture behavior [9,10], fatigue behavior [11,12], and shear response [13], and biocompatibility [14][15][16] of these cells. Research has also been dedicated to design methods of lattice structures, including creating functionally graded porous structures [4,[17][18][19], panel or sandwich-shaped lattice structures [20][21][22], and the mathematically designing algorithm [23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…The process aids in an excellent bonding between the particles, resulting in enhanced properties. The discrepancies concerning the properties obtained through theoretical and experimental approximations for SLM-manufactured structures can be minimized by adopting an FE based optimization route [95]. However, gradient auxetic structures made from SS316L powders using SLM have shown some inconsistencies concerning the porosity and the presence of unmelted grains [96].…”
Section: Slm and Dmlsmentioning
confidence: 99%